2022
DOI: 10.3390/medsci10030037
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Palmitoylethanolamide in the Treatment of Long COVID: A Real-Life Retrospective Cohort Study

Abstract: COVID-19 can cause symptoms that last weeks or months after the infection has gone, with a significant impairment of quality of life. Palmitoylethanolamide (PEA) is a naturally occurring lipid mediator that has an entourage effect on the endocannabinoid system mitigating the cytokine storm. The aim of this retrospective study is to evaluate the potential efficacy of PEA in the treatment of long COVID. Patients attending the Neurological Out Clinic of the IRCCS Centro Neurolesi Bonino-Pulejo (Messina, Italy) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…36 ARDS is the clinical equivalent of diffuse alveolar damage, a histopathological picture consistently found in patients who died from severe COVID-19. 13 One us (LR) was among the first in the international medical literature to propose the use of PEA in COVID-19 and long-COVID 37 ; subsequently, further research supported this rationale, [38][39][40] and revealed also its utility in inhibiting the Nod-like receptor family pyrin domain containing 3 inflammasome expression in cultured murine alveolar macrophages stressed by the spike protein of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), 41 as well as in inhibiting the entry of SARS-CoV-2, the etiological agent of COVID-19, into human cell lines by interacting with the spike protein and the angiotensin converting enzyme 2 receptors. 42 Moreover, the use of PEA in combination with luteolin improved olfactory dysfunction or mental clouding in a cohort of 69 patients (43 women, 26 men) with a mean age of 40.6 years affected by long-COVID, 43 and normalized γ-aminobutyric acid B -ergic activity and cortical plasticity in a further cohort of 39 long-COVID patients (26 women, 13 men) with a mean age of 49.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…36 ARDS is the clinical equivalent of diffuse alveolar damage, a histopathological picture consistently found in patients who died from severe COVID-19. 13 One us (LR) was among the first in the international medical literature to propose the use of PEA in COVID-19 and long-COVID 37 ; subsequently, further research supported this rationale, [38][39][40] and revealed also its utility in inhibiting the Nod-like receptor family pyrin domain containing 3 inflammasome expression in cultured murine alveolar macrophages stressed by the spike protein of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), 41 as well as in inhibiting the entry of SARS-CoV-2, the etiological agent of COVID-19, into human cell lines by interacting with the spike protein and the angiotensin converting enzyme 2 receptors. 42 Moreover, the use of PEA in combination with luteolin improved olfactory dysfunction or mental clouding in a cohort of 69 patients (43 women, 26 men) with a mean age of 40.6 years affected by long-COVID, 43 and normalized γ-aminobutyric acid B -ergic activity and cortical plasticity in a further cohort of 39 long-COVID patients (26 women, 13 men) with a mean age of 49.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a Kreb’s cycle intermediate, oxaloacetate, has also been tried, with some success in both ME/CFS and long COVID associated fatigue [ 195 ]. Even an endocannabinoid due to its anti-inflammatory potential have been studied—with some evidence of efficacy [ 196 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been published that palmitoylethanolamide is a direct and indirect antiviral agent against SARS-CoV-2. Nevertheless, evidence supporting its use in COVID-19 is limited and only based on a case series with no discussion of its utility for post-COVID-19 pain [121,122].…”
Section: Novel Pharmacological Treatmentsmentioning
confidence: 99%